Keanekaragaman dan Kerapatan Rumput Laut Alami Perairan Pulau Serangan Denpasar Bali - Herlinawati, Ni Desak Putu Dita; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.22-30, 2017)
Serangan Island was a costal area located in the Serangan village, South Denpasar district, near with Sanur and Nusa Dua tourism area. Serangan beach has a biodiversity such as natural macroalgae. This study was conducted in January 2017 at the seaweed cultivation area with the aims of research were to know the variety and density of macroalgae. The method used was a 1x1 m quadrat transect. Sampling was carried out during low tide. Macroalgae found in the area, consist of 12 species namely Ulva lactuca , Chaetomorpha linum. Chaetomorpha aera, Padina australis , Sargassum fluitans , Turbinaria ornate , Gelidium sp., Hypnea cornuta , Hypnea spicifera, Gracilaria salicornia , Acanthophora spicifera , Halimeda opuntia. Those species were belonging to 3 divisi namely Chlorophyta , Phaeophyta , Rhodophyta. The highest density of macroalgae was Padina australis while the lowest density was Chaetomorpha linum. Type of dominated macroalgae was from a group of Phaeophyta (brown algae) with highest dominance from the species of Padina australis. Water quality namely acidity (pH) was in the range of 7.54 to 7.75, salinity of 31.33-32.00 ppt, the water temperature was 26.50-27.30? C, which all was categorized as the optimal parameters for the growth of macroalgae. Assosiation of biota found were 9 species namely fish of larva, Cypraea lynx (Molusca) , Emerita sp., Halodule sp ., Synapta maculate, Enhalus acoroides, Cymodocea serrulata, Hermit crab, Ophiuroidea sp. The conditions coastal waters substrate was varied from white sand stone type to stony type by coral pieces.